Acceptability of risk stratification within population‐based cancer screening from the perspective of the general public: A mixed‐methods systematic review - Lily C. Taylor; Alison Hutchinson; Katie Law; Veeraj Shah; Juliet A. Usher‐Smith; Rebecca A. Dennison (Wiley, 2023)
Abstract Introduction Risk‐stratified cancer screening has the potential to improve resource allocation and the balance of harms and benefits by targeting those most likely to benefit. Public acceptability has implications for engagement, uptake and the success of such a programme. Therefore, this review seeks to understand whether risk stratification of population‐based cancer screening programmes is acceptable to the general public and in what context. Methods Four electronic databases were searched from January 2010 to November 2021. Qualitative, quantitative and mixed‐methods papers were eligible for inclusion. The Joanna Briggs Institute convergent integrated approach was used to synthesize the findings and the quality of included literature was assessed using the Mixed Methods Appraisal Tool. The Theoretical Framework of Acceptability was used as a coding frame for thematic analysis. PROSPERO record 2021 CRD42021286667. Results The search returned 12,039 citations, 22 of which were eligible for inclusion. The majority of studies related to breast cancer screening; other cancer types included ovarian, kidney, colorectal and prostate cancer. Risk stratification was generally acceptable to the public, who considered it to be logical and of wider benefit than existing screening practices. We identified 10 priorities for implementation across four key areas: addressing public information needs; understanding communication preferences for risk estimates; mitigating barriers to accessibility to avoid exacerbating inequalities; and the role of healthcare professionals in relation to supporting reduced screening for low‐risk individuals. Conclusion The public generally find risk stratification of population‐based cancer screening programmes to be acceptable; however, we have identified areas that would improve implementation and require further consideration. Patient or Public Contribution This paper is a systematic review and did not formally involve patients or the public; however, three patient and public involvement members were consulted on the topic and scope before the review commenced.